G254(P) Line infections in paediatric oncology patients: Our experience of biopatch. (7th April 2014) - Ritzmann, TA; Parsons, T; Majani, Y; Srinivasan, J; Wilne, SH
Abstract : Aims: To evaluate the incidence of line infections in a UK paediatric oncology centre and assess the efficacy of biopatch (a chlorhexidine impregnated exit site patch applied at line insertion) at reducing infections. Introduction: Central venous access is an essential component of paediatric oncology care however line insertion requires general anaesthesia and infections can be life threatening. Novel strategies to reduce line infections therefore merit evaluation. Methods: We audited the incidence of line infections before and after the introduction of biopatch. Data was collected retrospectively from electronic theatre records and hospital results systems over an 18 month period and each line was followed up for 6 months. We also investigated whether neutropaenia at insertion was associated with infection (chi-square test). Results: First six months (before biopatch): 45 patients had 64 lines inserted (1.42 per patient). 12 lines (19%) were removed due to proven infection. There were 9 exit site infections (0.14 per line) and 1 line was removed due to exit site infection alone. There were 33 blood culture positive infections (0.52 per line). Second six months (before biopatch): 47 patients had 52 lines inserted (1.11 per patient). 7 (13%) were removed due to proven infection. There were 18 exit site infections (0.35 per line) and 2 were removed as a result of this alone. There were 19 blood culture positive infections (0.37 per line). Third six months (post biopatch introduction): 45 patients had 52 lines inserted (1.15 per patient). 15 (28%) were removed due to proven infection. There was 1 exit site infection (0.02 per line) and no lines were removed on the basis of this alone. There were 37 blood culture positive infections (0.71 per line). In all time periods there was no association between neutropaenia (<0.5 x 10 9 /L) at the time of insertion and subsequent line infection (P = 0.71). Conclusion: Introducing biopatch reduced the number of exit site infections. There was no reduction in blood culture positive infections. There was no association between neutropaenia at the time of line insertion and subsequent line infection.